Successful retreatment of HCV relapse patient with 4 weeks long sofsobuvir, ribavirin, and daclatasvir combination: Case Series - Komal Saleem; Amjad Ali; Shazia Rafique; Noshaba Rani; Braira Wahid (BioScientific Review, 2020)
Hepatitis-C virus (HCV) is an enveloped RNA virus that currently infects more than 180 million people, worldwide. Interferon therapy was previously used as a standard therapy for HCV. Now it has been replaced with an interferon-free therapy or the direct acting antiviral (DAA) drug therapy. Although the DAA drug therapy is a potent strategy which has an excellent efficacy against the HCV infection with a majority of patients achieving sustained virological response (SVR), we report here three patients who experienced relapse after a 6-month long DAA drug therapy. The patients experienced relapse after receiving sofosbuvir (400mg) and ribavirin for 6 months. All three patients were later successfully treated with sofosbuvir, ribavirin, and daclatasvir combination. The current study highlights that the retreatment combination of sofosbuvir, ribavirin, and daclatasvir is more efficacious in the Pakistani population where practitioners are still using sofosbuvir and ribavirin.Copyright (c) The Authors